Bacteriological Safety of Blood Collected for Transfusion at University of Gondar Hospital Blood Bank, Northwest Ethiopia. (20th June 2013) - Wondimu, Hailegebriel; Addis, Zelalem; Moges, Feleke; Shiferaw, Yitayal
Abstract : Background . Transfusion associated bacterial infection has remained more frequent with a sever risk of morbidity and mortality. This study assessed the bacteriological safety of blood collected for transfusion. Method . A cross-sectional study was conducted at University of Gondar hospital blood bank from December 2011 to June 2012. Bacterial isolation, identification, and antimicrobial susceptibility tests were done as per the standard procedure. Chi-square test and P value were used to assess associations between risk factors and the bacterial isolation rate. Results . Twenty-one (15.33%) blood units were found contaminated with bacteria, and 95.24% contamination was due to external sources. The commonly isolated bacteria were Staphylococcus aureus, Coagulase negative Staphylococci, Escherichia coli, Klebsiella species, Streptococci species, Enterobacter species, and Citrobacter species. All of the bacteria isolated were 100% sensitive to Gentamicin, Chloramphenicol, Amoxicillin, and Doxycycline. Multiple antimicrobial resistances were observed in 66.7% of the isolates. Not using glove by phlebotomist, touching disinfected phlebotomy site and double puncture at the same hand or both hands of a donor were found to be risk factors for bacterial contamination. Conclusion . Bacterial contamination of blood to be transfused is a common problem in the hospital. So attention should be given to activities performed at the blood bank for safe transfusion practices.